Not-prescribed Use of Herbal Products and Supplements Among Pregnant Women - Misa Naghdipour Mirsadeghi; Zahra Rafiei Sorouri; Mandana Mansour Ghanaie; Fatemeh Hosseinzadeh; Sara Farzadi; Gelareh Biazar; Seyed Mohamadreza Tabatabaei Taher (Journal of Holistic Nursing and Midwifery)
Introduction: Not-prescribed use (NPU) of herbal products and supplements during pregnancy is a potent risk for both mother and fetus and a big challenge for anesthesiologists. However, little is known about this topic in Guilan Province, Iran. Objective: This study aimed to determine how pregnant women take supplements and herbal medications. Materials and Methods: This analytical cross-sectional study was conducted in 2022. Eligible pregnant women enrolled in the survey, and a checklist containing items about maternal demographic data and the maternal pattern of herbs and supplements used during pregnancy was filled out through a face-to-face interview. Multivariate logistic regression, the Chi-square, and the Mann-Whitney U statistical tests were used to analyze the data. Results: The data from 682 women were analyzed. A total of 488 women (71.6%) were less or equal to 30 years old; 498(73%) lived in urban areas; 508(74.5%) were homemakers; 444(65.1%) had under-diploma or diploma education, 292(42.8%) were gravid one or 251(36.8%) gravid two. In addition, 25.1% reported using at least one herbal remedy during pregnancy, and 90% took supplements; 0.7% had NPU of supplements and 93.6% took herbal products. About 10% did not take any supplements. Iron (23.3%) and folic acid (23.1%) were the most frequently taken supplements, and thyme (20.2%) and mint (17.5%) were the most commonly taken herbs. Using logistic regression, we found that urbanization (OR=1.91, 95% C, 1.6%, 3.14%, P=0.01), employment (OR=2.21, 95% CI; 1.46%, 3.33%, P=0.0001), and higher gravidity (OR=2.03, 95% CI; 1.22%, 3.36%, P=0.006) increases the probability of consuming supplements and herbal products during pregnancy. Conclusion: The lack of physicians’ supervision of the herbal therapy process among pregnant women in an academic center was worrying. However, most women received the supplements based on healthcare professionals’ advice. A few women did not take essential supplements.